Pulmonary fungal co-infection prevalence among Iranian patients with pulmonary tuberculosis: a systematic review and meta-analysis - Mortazavi, Hamed; Ghazalibina, Mehran; Mansouri, Shamseddin; Khaledi, Azad; Saburi, Ehsan (Penerbit Universiti Kebangsaan Malaysia, 2019)
Tuberculosis (TB) is further aggravated if it is accompanied with fungal co-infection. This study aimed to evaluate the prevalence of pulmonary fungal co-infection among Iranian patients with pulmonary TB using a systematic review and meta-analysis. The present study was a review of cross-sectional studies on the prevalence of pulmonary fungal co-colonization among Iranian patients with pulmonary TB with regard to the PRISMA Protocol. To this end, the articles published online in English and Persian were searched on the main databases and gateways such as Google Scholar, Science Direct, Web of Science, MEDLINE, PubMed, SCOPUS, Cochrane Library, Magiran, Irandoc, and Scientific Information Databases. The reviews of the literatures published online from 2000 to the end of 2018 were included in the study. The keywords used for searching through the databases were pulmonary fungal co-infection with pulmonary TB, pulmonary mycosis co-infection with pulmonary TB, pulmonary fungal colonization/agents with pulmonary TB, AND Iran. Finally, the collected data were analyzed by Comprehensive Meta-Analysis software. The analyses showed that the prevalence of fungal co-infection among patients with pulmonary TB varied from 12.3-68.8%, and that the combined prevalence of fungal co-infection among patients with pulmonary TB was 17.4%. Amongst the fungi involved in co-infection with TB, Candida spp. was the most predominant with the prevalence of 6.9%, followed by Aspergillus spp. (3.2%). Moreover, the highest prevalence of Aspergillus spp. was observed for Aspergillus fumigatus (1.6%). The most frequent Candida spp. was Candida albicans with a frequency of 6%. The findings showed that the combined prevalence of fungal co-infection among Iranian patients with pulmonary TB was high. In this regard, among the fungi involved in co-infection with TB, Candida spp. was the most frequent.